Benefits of a novel highly bioavailable resveratrol formulation, JOTROL, for Alzheimer's disease: Nonhuman/Lead optimization studies. (7th December 2020) - Volmar, Claude‐Henry; Dennison, Jessica; Ricciardi, Natalie R.; Janczura, Karolina J.; Walker, Brittni R.; Brown, Jonathan M.; Stahl, Jack; Hayward, Marshall A.; Brothers, Shaun P.; Wahlestedt, Claes
Abstract: Background: With the recent Alzheimer's disease (AD) clinical trial shortcomings, we and colleagues agree that an epigenetic approach is needed to address the polygenicity of AD. Recently, a randomized clinical trial with the SIRT1 activator resveratrol (3, 5, 4'‐trihydroxy‐trans‐stilbene) has shown positive effects in AD patients (Turner et al., 2015; Moussa et al., 2017). However, the high dose needed due to low bioavailability has been reported to cause a GI side effect. To increase bioavailability, JOTROL, a new oral formulation of resveratrol that shows significantly better pharmacokinetic properties than non‐formulated resveratrol, was manufactured by Jupiter Orphan Therapeutics. We hypothesize that equimolar concentrations of JOTROL, compared to non‐formulated resveratrol, will result in greater brain exposure to resveratrol and more efficacious responses on AD biomarkers, allowing for a reduction in dose regimen. Methods: For acute studies, Sprague Dawley rats or C57B6 mice (n = 3/treatment) were administered a single oral dose of 50 mg/kg JOTROL 30 minutes prior to being euthanized. Blood, buffy coat and brains were harvested. For AD‐related studies, 15‐month‐old male triple‐transgenic (APPSW /PS1M146V /TauP301L ; 3xTg‐AD) AD mice were treated by daily oral gavage with 50 mg/kg JOTROL (n = 5) or vehicle (n = 5) for 36 days. Animals were euthanized after behavior tests. The expression of AD‐related genes and proteins in brain, liver and spleen were analyzed using RT‐qPCR, Western blots and ELISAs. Effects on mitochondrial biogenesis were also investigated. Results: JOTROL (50 mg/kg) increases brain and plasma resveratrol bioavailability in animals, significantly increases both SIRT1 (P<0.0001) and α‐secretase ADAM10 (P<0.0001) gene expression in rat brain, but significantly decreases Tau gene expression (P<0.05). 36‐day treatment of 3xTg‐AD mice with 50 mg/kg JOTROL decreases expression of IL6 (P<0.001 in liver, P<0.05 in spleen) and TNFα (P<0.001 in liver and P<0.01 in spleen), concurrent with a marked decrease of splenomegaly. Increased mitochondrial biogenesis is also observed in the brain (P<0.05) and in the liver (P<0.05) of these mice. Conclusions: JOTROL has a strong anti‐inflammatory effect in the brain and peripheral organs, promotes non‐amyloidogenic processing of the amyloid precursor protein and increases mitochondrial biogenesis. Further investigation is underway to determine prophylactic effects of JOTROL for AD pathogenesis.